Recent changes in landscape structure and function in a Mediterranean region of SW Spain (1950–1984) - Ales, R. F.; Martin, Angel; Ortega, Fernando; Ales, E. E. (Landscape Ecology, 1992)
Recent economic development has altered landscape structure and function of a mediterranean region in Southwestern Spain. Intensive agricultural systems have concentrated in the more fertile areas, while margi- nal ones have been abandoned. As a result, landscape structure has changed. Consequences of this structural change on landscape processes are discussed.
Keywords: agroecology; biological conservation; dofiana national park; guadalquivir valley; sierra morena; Spain